Effect of non-metal promoters on higher alcohols synthesis from syngas over Cu-based catalyst. Issue 6 (December 2018) - Liu, Yong-Jun; Deng, Xuan; Huang, Wei
Abstract: A series of non-metal promoted Cu-based catalysts were prepared and tested for the synthesis of higher alcohols from syngas in slurry bed reactor. The catalysts were characterized by XRD, 27 Al-MAS-NMR, H2 -TPR, NH3 -TPD, CO2 -TPD, TG-DTG and XPS techniques. Results showed that non-metal promoters mainly adjusted the acidity/basicity and the Cu content on catalysts surface, which played an important role in higher alcohols formation. Activity results showed that the syngas could be directly catalyzed to higher alcohols over CuZnAl catalyst. Also, it was found that acidic tartaric acid (TA) promoted methanol synthesis, whereas alkaline triethanolamine (TEA) favored the formation of C2+ OH selectivity which reached approximately 48.0%. Graphical abstract: Highlights: Non-metal promoters had significant influence on the catalytic performance. TEA favored the higher alcohols formation. TA promoted the formation of methanol. Higher alcohols formation required a suitable amount of weak acid and higher Cu content.